Peran Mahasiswa Sebagai Fasilitator Puspaga Dalam Upaya Mendekatkan Pelayanan Publik Di Balai RW Kelurahan Perak Barat Surabaya - Aulia Nisya Salshabila,; Eddy Wahyudi, (Student Scientific Creativity Journal, 2023)
This research aims to determine the role of students as Puspaga facilitators in an effort to bring public services closer to the RW Hall, Perak Barat Subdistrict, Surabaya. Puspaga services are a means of learning and counseling for parents in Surabaya to improve their ability to overcome problems related to violence against children, delinquency among children and other problems that exist in the family environment. So Puspaga services are provided at the Perak Barat Village RW Hall, which is one of the innovations of the Surabaya City Government to bring public services closer to the community. This research uses a qualitative approach with descriptive research methods. Data in this research data collection techniques were carried out by means of observation, interviews and taking documentation. The results of the research that has been carried out show that Puspaga Facilitators have been able to provide closer services to the community by providing Puspaga Balai RW services in Perak Barat Subdistrict which include counseling services, socialization and parenting classes.